Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1186/s40734-018-0070-x
|View full text |Cite
|
Sign up to set email alerts
|

Crossing barriers: a multidisciplinary approach to children and adults with young-onset movement disorders

Abstract: BackgroundDiagnosis of less common young-onset movement disorders is often challenging, requiring a broad spectrum of skills of clinicians regarding phenotyping, normal and abnormal development and the wide range of possible acquired and genetic etiologies. This complexity often leads to considerable diagnostic delays, paralleled by uncertainty for patients and their families. Therefore, we hypothesized that these patients might benefit from a multidisciplinary approach. We report on the first 100 young-onset … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In our study there seems to be a discrepancy with the results of prior studies in French patients in which choreoathetosis and ataxia were noted in all patients 20 and in USA patients in which ataxia was noted in 68% of patients 11 . Phenomenological assessment of movement disorders may be very challenging in childhood; this was suggested by authors of the former study for AHC patients (Bourgeois et al 20 ) and was further highlighted by a recent study that reported on young-onset movement disorders patients referred to a multidisciplinary outpatient clinic 21 . The advantage of our study is its prospective nature with clinical examination particularly focalized in assessment of movement disorders, completed by a further blinded video-based analysis of phenomenology by our second movement disorder expert.…”
Section: Discussionmentioning
confidence: 99%
“…In our study there seems to be a discrepancy with the results of prior studies in French patients in which choreoathetosis and ataxia were noted in all patients 20 and in USA patients in which ataxia was noted in 68% of patients 11 . Phenomenological assessment of movement disorders may be very challenging in childhood; this was suggested by authors of the former study for AHC patients (Bourgeois et al 20 ) and was further highlighted by a recent study that reported on young-onset movement disorders patients referred to a multidisciplinary outpatient clinic 21 . The advantage of our study is its prospective nature with clinical examination particularly focalized in assessment of movement disorders, completed by a further blinded video-based analysis of phenomenology by our second movement disorder expert.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the number of possible aetiologies is growing, especially those concerning genetic causes. Owing to a variable phenotype–genotype correlation, the diagnostic process for PMDs becomes challenging and time consuming, not only for the clinician but also for patients and caregivers 2 …”
Section: Figurementioning
confidence: 99%
“…Owing to a variable phenotype-genotype correlation, the diagnostic process for PMDs becomes challenging and time consuming, not only for the clinician but also for patients and caregivers. 2 Innovative next-generation sequencing (NGS) techniques have increased the diagnostic yield in paediatric neurology. 3 The use of NGS can speed up the diagnostic process and prevent unnecessary additional investigations, and shorten the time of uncertainty in patients and caregivers.…”
mentioning
confidence: 99%
“…Diagnosis is made even harder in adulthood, given that information on the potential perinatal injury and the results of childhood investigations are often lacking more than 15 years later. Taking into account the huge progress in medical knowledge and diagnostic tools during the last two decades, we think that the transition from pediatrics to adult neurology may represent a good opportunity to reappraise the diagnosis with a multidisciplinary approach . Dedicated transition care programs in neurology may foster this diagnosis reappraisal …”
Section: Treatable Causes Of Movement Disorders That May Mimic Cpmentioning
confidence: 99%
“…Taking into account the huge progress in medical knowledge and diagnostic tools during the last two decades, we think that the transition from pediatrics to adult neurology may represent a good opportunity to reappraise the diagnosis with a multidisciplinary approach. 5 Dedicated transition care programs in neurology may foster this diagnosis reappraisal. 6 In the current issue, Ros-Castelló et al report the case of a 52-year-old woman misdiagnosed as CP, who actually had GLUT1 deficiency.…”
mentioning
confidence: 99%